Development of Nature-Themed Language Literacy Teaching Materials to Enhance Language Skills and Environmental Awareness of Elementary School Students - Hanifah, Ifah; Isroyati, Isroyati; Thi Thuy Trang, Ton (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
The objective of this study is to develop and test the effectiveness of nature-themed language literacy teaching materials that are relevant, engaging, and able to foster environmental awareness among elementary school students. The method used is the Research and Development (R&D) model proposed by Jolly and Bolitho, involving 30 fifth-grade students and teachers at SDN 1 Bungurberes, Kuningan. Data were collected through questionnaires, interviews, expert validation, and pretest–posttest instruments. The results show that 83% of students prefer nature-themed readings and that teachers need contextual materials supported by illustrations and character-building content. Expert validation indicates a high feasibility level of 88.5%, while the effectiveness test shows a significant increase in students’ literacy scores from 64.3 to 81.7, with 89% student satisfaction. Furthermore, the module effectively enhances ecological awareness, with 85.5% of students demonstrating positive attitudes toward environmental care. The novelty of this study lies in integrating literacy skill development with ecological character education through contextual, nature-based materials that reflect students’ real-life experiences. These findings confirm that the materials developed are valid, practical, and effective in improving literacy skills and fostering environmental awareness of elementary school students.